ANALISIS PELUANG PILIHAN KELEMBAGAAN PEMASARAN KAKAO DI PROVINSI SULAWESI TENGAH - Novia Dewi Dewi (Indonesian Journal of Agricultural Economics, 2012)
The policy objectives for cacao agribusiness development in the Province of CentralSulawesi was directed toward the improvement of production and farm income. In factthere were so many cases that had becoming obstacles in these efforts, such as lowprices of outputs, while the capital of the farmers was relatively low. The objectives ofthis study were to: (1) Analyze the opportunity of market agent cacao, (2) Know theopportunity of market agent cacao was relatively efficient and margin contribution ofthe family profit on cacao farming. The results of this study indicated that: (1)Educational, land use, production, income, and the number of their family memberfactor had affected upon the farmers choice a market agent, (2 ) The change of price atthe farm level was fluctuated lower than those price change at the collector agent orexporter level. It had indicated that in cacao marketing there were still monopsony oroligopsony power, and the benefit of a higher price were mostly enjoyed by theexporter.Keyword: opportunity of market agent, price, monopsony